2010
DOI: 10.1111/j.1365-2036.2009.04184.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy‐controlled intra‐individual comparisons to screen relevant neoplasia: faecal immunochemical test vs. guaiac‐based faecal occult blood test

Abstract: SUMMARY BackgroundGuaiac-based faecal occult blood tests (g-FOBTs) are most commonly used in colorectal cancer (CRC) screening programmes. Faecal immunochemical tests (FITs) are thought to be superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 33 publications
0
48
0
2
Order By: Relevance
“…14, 27). One should take into account, however, that these studies have been conducted in populations quite different from our study population, as both studies investigated symptomatic subjects with a higher mean age than our group (14,27). It is known that FITs carried out in symptomatic subjects yield higher sensitivities (28).…”
Section: Discussionmentioning
confidence: 87%
“…14, 27). One should take into account, however, that these studies have been conducted in populations quite different from our study population, as both studies investigated symptomatic subjects with a higher mean age than our group (14,27). It is known that FITs carried out in symptomatic subjects yield higher sensitivities (28).…”
Section: Discussionmentioning
confidence: 87%
“…After initial screening of titles and abstracts, 113 papers were considered to be potentially relevant and ordered for full-paper screening; of these, 21 papers 13,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] were included in the review.…”
Section: Results Of the Assessment Of Clinical Effectiveness Assessmentmentioning
confidence: 99%
“…Five diagnostic cohort studies, 13,52,53,55,58 reported in 17 publications, 13,52,53,55,[58][59][60][61][62][63][64][67][68][69][70]73,74 provided data on the diagnostic performance of the OC-Sensor FIT assay. All five studies 13,52,53,55,58 reported accuracy data, for which CRC was the specified target condition, 13 53,55 Three studies reported additional accuracy data various non-malignant and composite target conditions.…”
Section: Details Of Oc-sensor Studiesmentioning
confidence: 99%
“…Between 70% and 90% of CRC originates from adenomatous polyps, and early detection and removal of these precancerous adenomas significantly decrease CRC incidence and mortality [43]. Therefore, current CRC screening aims for early detection of CRC, and those adenomas with a high risk of malignant transformation (advanced adenomas) [44]. In screening tests, individuals with a positive fecal immunological test (FIT) are referred for colonoscopy (gold standard).…”
Section: Colorectal Cancermentioning
confidence: 99%